2017
DOI: 10.17503/agrivita.v39i3.646
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Organic and Inorganic Fertilizers on the Growth and Yield of Green Bean, Phaseolus vulgaris L. Grown in Dry and Rainy Season

Abstract: Research aimed to study the influence of organic and inorganic fertilizers on growth and yield of green bean (Phaseolus vulgaris L.). It was conducted in Andisol soil, Batu, East Java, 900 m above sea level, 24-27 ⁰ C for dry season (from May to July 2013) and rainy season (from January to March 2014). A randomized block design was used to arrange five treatments such as 1) no fertilizers applied; 2) five t ha -1 cow manure; 3) 10 t ha -1 cow manure; 4) 50 kg N ha -1 , 150 kg P 2 O 5 ha -1 and 50 kg K 2 O ha -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…High productivity of common bean mainly relies on external N inputs due to its poor BNF capacity. The productivity of common bean crops appeared compromised in organic cultivation systems [118,120], where the timing of N supply is remarkably challenging because the mineralisation rates of organic manures is weather-and soil-dependent. In contrast, no significant variations in yield of common bean were found in organic or inorganic fertigation managements in the studies of Uyanoz [121], Karunji et al [122], and Magalhaes et al [123].…”
Section: Fertilizationmentioning
confidence: 99%
“…High productivity of common bean mainly relies on external N inputs due to its poor BNF capacity. The productivity of common bean crops appeared compromised in organic cultivation systems [118,120], where the timing of N supply is remarkably challenging because the mineralisation rates of organic manures is weather-and soil-dependent. In contrast, no significant variations in yield of common bean were found in organic or inorganic fertigation managements in the studies of Uyanoz [121], Karunji et al [122], and Magalhaes et al [123].…”
Section: Fertilizationmentioning
confidence: 99%
“…Shallow of water table has been recognized as one limiting factor to plant growth and development (Lawson & Matthews, 2020) since it created partially hypoxic condition within rhizosphere. In favorable condition, snap bean was responsive to fertilizer application (Santosa, Maghfoer, & Tarno, 2017) but bean plant was less responsive under SWT exposure. Damage to roots directly reduces water potential and turgor in cells of above ground organs.…”
Section: Role Of Ala In Overcoming Stress Due To Swt Exposurementioning
confidence: 94%
“…Based on the results of investigations, it was found that the combine application of organic and inorganic fertilizer significantly increased the crops yield compare to isolat application of them [17,34,35,36], but Santosa et al [37] founded in his research that the use of 50: 150: 50 kg ha -1 dose of NPK, produced the high value of plant height (PH), pods per plant (PP) and growth attributes on grean bean against to the application of cow manure and control.…”
Section: Introductionmentioning
confidence: 99%